Interaction of ions with the luminal sides of wild-type and mutated skeletal muscle ryanodine receptors - Schilling, Roman; Fink, Rainer; Fischer, Wolfgang (Journal of molecular modeling, 2016)
Ryanodine receptors (RyRs) are the largest known ion channels, and are of central importance for the release of Ca2+ from the sarco/endoplasmic reticulum (SR/ER) in a variety of cells. In cardiac and skeletal muscle cells, contraction is triggered by the release of Ca2+ into the cytoplasm and thus depends crucially on correct RyR function. In this work, in silico mutants of the RyR pore were generated and MD simulations were conducted to examine the impact of the mutations on the Ca2+ distribution.
Gesehen am 14.05.2020